'PERFSCORE' – a multidimensional score: a simple way to predict the success of cardiac rehabilitation. Issue 8 (August 2017) - Maras, Patrizia; Doimo, Sara; Altinier, Alessando; Della Mattia, Alessio; Scudeller, Luigia; Sinagra, Gianfranco; Klersy, Catherine
Abstract : Background: We propose a simple and reliable score, performance score ('PERFSCORE'), that allows cardiologists to assess the achievement of therapeutic goals. Methods: We identified six indicators of cardiac rehabilitation performance: heart rate (HR) less than 70 beats/min; blood pressure (BP) less than 140/90 mmHg; smoking cessation or non-smokers; left ventricular ejection fraction (LVEF) more than 40%; LDLc less than 100 mg/dl or more than 70 mg/dl if diabetic; and on treatment at least with three drugs among angiotensin converting enzyme (ACE) inhibitors or angiotensin receptor blocker (ARBs), β-blockers, statins, and ASA. These six indicators are considered to be the collective expression of a latent variable measuring performance. To assess the relative contribution of each indicator in the definition of cardiac rehabilitation performance, we fitted a structural equation model using the 'Stata 13' system. Results: A total of 839 consecutive patients were analyzed; 49% had recent ST- elevation myocardial infarction/non-ST elevation myocardial infarction and 51% had undergone elective percutaneous coronary intervention/coronary artery bypass graft. At the end of cardiac rehabilitation, LVEF was 55 ± 11%; HR, 69 ± 13 beats/min; SBP, 135 ± 20 mmHg; DBP, 79 ± 10 mmHg; LDLc, 88 ± 29 mg/dl; 56% had stopped smoking; 71% were on β-blockers; 78% ACE inhibitors or ARBs; 87% were on statins, and 96% were on ASA. Weights for each indicator in the PERFSCORE were 0.57 for HR, 0.40 for BP, 0.87 for LVEF, 0.78 for smoking, 0.42 for LDLc, and 0.75 for drugs, multiplied by 1 if the target has been reached, otherwise by 0. Higher performance values correspond to better cardiac rehabilitation results. The point range was 0–36: less than 24, not satisfying cardiac rehabilitation; 24–29, satisfying cardiac rehabilitation; and more than 29, optimal cardiac rehabilitation. Conclusion: In conclusion, we propose an easy algorithm to calculate the success of cardiac rehabilitation.